Lost in translation? Building science and innovation city strategies in Australia and the UK - Couchman, P.; McLoughlin, I.; Charles, David (eContent Management Pty Ltd, 2008)
With the development of the ‘knowledge economy’ in many advanced industrial nations, there hasbeen a growing interest in regional innovation systems and the role that universities might play inthese. One result has been the demarcation by government actors of specific spaces for the creation,transfer and transformation of knowledge. Such spaces have been given various names, such as‘smart regions’, ‘science cities’ and ‘innovation corridors’. Whilst the associated policy rhetoric hasmuch in common with the earlier interest in science and technology parks there are also clear distinguishing differences. More recent policy initiatives have sought to foster industry clusters withinthese spaces to contribute to economic development and diversification and link this to economic,social and cultural regeneration. This paper explores policy-driven creation of ‘innovation areas’ byfocusing on two contrasting examples: Newcastle Science City in the North East of England andthe Gold Coast Pacific Innovation Corridor in Queensland, Australia. The paper compares the rhetoric of university–industry–government policies with the realities.